Changes of metabolic profile in men treated for androgenetic alopecia with 1 mg finasteride - Duskova, M; Hill, M; Starka, L (Endocrine regulations, 2010)
OBJECTIVE: Androgenetic alopecia is recognized as a risk factor for cardiovascular diseases, glucose metabolism disorders, and benign prostate hyperplasia and/or carcinoma. Finasteride, used for treatment of androgenetic alopecia at a dose of 1mg/day, is an effective inhibitor of type II 5alpha-reductase, the enzyme responsible for the reduction of testosterone to dihydrotestosterone. Recent studies reported that dihydrotestosterone, among other activities, might play some role in visceral fat metabolism. It thus seemed reasonable to examine whether finasteride treatment of androgenetic alopecia ameliorates some features of metabolic syndrome frequently seen associated with this condition. METHODS: We examined 12 men with premature balding (defined as frontoparietal and vertex hair loss before age 30 with alopecia defined as grade 3 vertex or more on the Norwood-modified Hamilton alopecia classification). Hormonal levels and metabolic parameters were determined and insulin tolerance tests performed for all individuals. Finasteride (1 mg/day) was administrated for 12 months. The hormonal profile and lipid spectrum were monitored after 4, 8 and 12 months of treatment and insulin tolerance tests were repeated after 12 months of the treatment. RESULTS: After treatment with finasteride the expected changes in the steroid spectrum were seen, namely a decrease in dihydrotestosterone and increase in testosterone, androstenedione and free testosterone index. We observed an initial increase in total cholesterol and HDL- and LDL-cholesterol, which stabilized with prolonged treatment. We founded a significant decrease in glycated hemoglobin HbA1c and insulin resistance measured using rate constant for plasma glucose disappearance (kITT) showed only a borderline decrease. CONCLUSIONS: Finasteride is an efficient 5alpha-reductase inhibitor even at low doses of 1 mg/day. In men treated with this dose for 12 months, we observed mild differences in metabolic profile with slight amelioration of glucose metabolism regulation.
Keywords: Glycated Hemoglobin; androstendion; alopecie; inzulinová rezistence; Humans; lidé; Lipids; Alopecia; lipidy; 3-Oxo-5-alpha-Steroid 4-Dehydrogenase; Treatment Outcome; krevní glukóza; Time Factors; finasterid; Testosterone; časové faktory; testosteron; inhibitory 5-alfa-reduktasy; Adult; Blood Glucose; Male; Glycated Hemoglobin A; Biomarkers; Androstenedione; výsledek terapie; mužské pohlaví; Finasteride; Severity of Illness Index; glykovaný hemoglobin; Enzyme Inhibitors; 3-oxo-5-alfa-steroid-4-dehydrogenasa; stupeň závažnosti nemoci; dospělí; biologické markery; inhibitory enzymů; 5-alpha Reductase Inhibitors; Insulin Resistance